Effects of Cr content on the corrosion behaviour of porous Ni–Cr–Mo–Cu alloys. (18th August 2021) - Li, Xide; Yang, Junsheng; Hu, Yangdon; Zou, Haoran; Zhang, Chuo; Liu, Yuzuo; Xiong, Lieqiang; Ye, Jianping
ABSTRACT: The porous Ni-Cr-Mo-Cu alloys were fabricated by an activation reaction sintering technique. The effects of Cr content varied from 10 to 30 wt-% on the corrosion performance of porous alloys in 10 wt-% H2 SO4 solution were evaluated using weight-loss method and electrochemical techniques. The structural morphology, phase constitution and elemental distribution were characterized by scanning electron microscopy (SEM), X-Ray diffraction analysis, energy dispersive spectrometer and X-ray photoelectron spectroscopy (XPS). The results indicate that porous Ni-Cr-Mo-Cu alloys possess excellent corrosion performance. With incremental changes in Cr contents, the anticorrosion ability increases as well. Electrochemical measurements illustrate results similar to that of weight-loss method, with the increment of Cr content, the double capacitive loops for the porous alloy increases as well, which illustrate that the corrosion procedure is controllable by electrochemical reaction. Moreover, the charge transfer resistance of Ni30wt-%Cr10wt-%Mo5wt-%Cu is 49.2 times bigger than that of Ni10wt-%Cr10wt-%Mo5wt-%Cu. And the corrosion mechanism was explored by XPS.